Evaluation of the Routs of Oral Health Information Being Delivered to Yazd Population in 2011 - Ahamd Haerian; SeyedSaeid Mazloomy Mazloomy Mahmoudabad; Amirmohammad Mahabadi; Hamidreza Dehghan; Zeinab Hamzehei (Shahid Sadoughi University of Medical Sciences, 2013)
Introduction: The discipline of oral public health is known as a science and art of dealing with populationoral health. In order to improve public awareness followed by changing people`s life style itis necessary for the society to be exposed to massive oral health information.The aim of this study was to evaluate the routes of oral health information being delivered to the Yazd population in1389 Materials and Methods: In this descriptive cross sectional study 16 blocks in urban areas of Yazd city were randomlyselected. A total of 400 subjects (8 years and above) were interviewed and thequestionnaire filled. The data were analyzed using descriptive analysis with SPSS 18software. Results:Two hundred and twenty four male subjects (56%) and 173 female subjects (44%)participated in this study. According to this study the main sources of oral healthinformation on Yazd population where mass media (radio & television) (22.3%) and dentists(14.5%). It was also believed that radio and television and dentists were potential sources oforal health information. It was revealed that 67.5% of the population had access to theinternet. The use and the potential of internet for access to oral health information were insixth place. Conclusion: Oral health officials put more time andeffort for providing oral health programs in order to improve oral health conditions in thesociety. Science using the internet as a source of oral health information for access in thesociety was less important than some other countries are main due to, language problems,investment in this area is recommended.